THE IMPLEMENTATION OF 5S CULTURE AS AN EFFORT TO FORM STUDENT CHARACTER - Pratiwi, Woro Yustia; Anshari, Ari (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
The 5S culture is self-habituation to always senyum means to smile, sapa means to greet, salam means to say hello in islam, sopan means to be polite, and santun means to courteous. This study aims to get a clearer and more complete picture and information regarding the attitudes of students in schools in implementing 5S culture. The research subjects were students of SMA Batik 1 Surakarta, SMA Muhammadiyah 1 Surakarta, and SMA Muhammadiyah 3 Surakarta. This type of research uses qualitative methods through a case study approach. The result of the research is that students implement the 5S culture even though in certain conditions they are still exceeding the limit.